Nasal carriage of staphylococcus aureus in families of children on peritoneal dialysis - Oh, Jun; Baum, Heike von; Klaus, Günter; Schaefer, Franz (Advances in peritoneal dialysis, 2000)
Nasal carriage of Staphylococcus aureus is a risk factor for catheter-related infections with S. aureus in patients on chronic peritoneal dialysis (CPD). In children, S. aureus may transmitted to the catheter either from the patients’ nares, or from the nares of caregiving carriers. As part of a prospective trial on the efficacy of mupirocin prophylaxis in children on CPD and their caregivers, we evaluated the prevalence of S. aureus carriage in 92 families of pediatric CPD patients.